Gender-related differences in patients with acute aortic dissection type A - Rylski, Bartosz; Büsch, Christopher (The journal of thoracic and cardiovascular surgery, 2021)
Acute aortic dissection type A can occur in both genders at any age. Our aim was to report differences in presentation, treatment, and outcome in female and male patients with acute aortic dissection type A. Methods Between July 2006 and June 2015, 56 centers participating in the German Registry for Acute Aortic Dissection Type A reported on a total of 3380 patients. As many as 1234 (37%) were women and 2146 (63%) were men. We compared their clinical features and events occurring within 30 days after surgery. Results Women were significantly older than male patients (65.5 ± 12.7 years vs 59.2 ± 13.3 years; P < .001). Aortic dissection extended down to the abdominal aorta in 43% men and 39% women (P = .01). Visceral (4.9% vs 7.3%; P = .006) and renal malperfusion (7.7% vs 10.6%; P = .006) were more frequently diagnosed in men. Aortic roots were replaced more frequently in men (22% vs 18%; P < .001). Different aortic arch repair strategies were distributed similarly in both genders. The incidence of new hemiplegia or hemiparesis was also similar in men and women (P = .24). Thirty-day mortality did not differ between women and men (16.3% vs 16.6%; P = .18). In a logistically mixed-effect model, gender revealed no influence on 30-day mortality (odds ratio, 1.15; 95% confidence interval, 0.92-1.44; P = .21). Conclusions Aortic dissection type A occurs almost twice as frequently in men. Women develop aortic dissection later in life. Despite women and men presenting at different ages and exhibiting varying dissection and malperfusion patterns, and the fact that men undergo complex proximal aortic repair more frequently, outcomes are similar in both genders.